PERAN GURU PENDIDIKAN AGAMA ISLAM TERHADAP PENDIDIKAN KARAKTER SISWA DI SMA SULTAN AGUNG KASIYAN- PUGER-JEMBER TAHUN PELAJARAN 2016/2017 - Tamami, Badrut (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
This case study aims to explore (1) the role of religious-subjects teachers in building students’ character, (2) problems faced by the teachers in doing so, and (3) a number of solutions that may be used to solve the problems. Three approaches were carried out to collect the data: participant observation, interview, and documentation. The data analysis technique is done in three ways: data reduction, data serving (display), and inferencing. The validity of the data obtained was ensured through referential sufficiency and triangulation to espouse the criteria of credibility, transferability, dependability, and confirmability. The study was conducted at SMA Sultan Agung in Kasiyan Puger. The results of this study shows that both internal and external elements were involved. The internal elements included the principal, the vise principal for curriculum design, and all teachers, while the external element includes foundation, school committee and figures of local society. Keyword: Teachers of Islamic Religion Education, Character Building